Of Narratives and Artifacts - Venkataraman, Sankaran; Sarasvathy, Saras D.; Dew, Nicholas; Forster, William R. (Academy of Management Review, 2013)
In a thoughtful commentary on our recent article, Garud and Giuliani (2013) spotlight a narrative perspective on understanding entrepreneurial opportunities.